Probing the interactions of CdTe quantum dots with pseudorabies virus - Du, Ting (Sci Rep, 2015)
Quantum dots (QDs) have become one of the most promising luminescent materials for tracking viral infection in living cells. However, several issues regarding how QDs interact with the virus remain unresolved. Herein, the effects of Glutathione (GSH) capped CdTe QDs on virus were investigated by using pseudorabies virus (PRV) as a model. One-step growth curve and fluorescence colocalization analyses indicate that CdTe QDs inhibit PRV multiplication in the early stage of virus replication cycle by suppressing the invasion, but have no significant effect on the PRV penetration. Fluorescence spectrum analysis indicates that the size of QDs is reduced gradually after the addition of PRV within 30 min. Release of Cd(2+) was detected during the interaction of QDs and PRV, resulting in a decreased number of viruses which can infect cells. Further Raman spectra and Circular Dichroism (CD) spectroscopy analyses reveal that the structure of viral surface proteins is altered by CdTe QDs adsorbed on the virus surface, leading to the inhibition of virus replication. This study facilitates an in-depth understanding of the pathogenic mechanism of viruses and provides a basis for QDs-labeled virus research.